2019
DOI: 10.6090/jarq.53.59
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective and Histopathological Studies of <i>Entamoeba</i> spp. and Other Pathogens Associated with Diarrhea and Wasting in Pigs in Aichi Prefecture, Japan

Abstract: known to be involved in postweaning wasting (Ellis et al. 1998, Järveots et al. 2016). Salmonellosis, particularly that associated with Salmonella Typhimurium and Salmonella Choleraesuis, can occur concurrently with PMWS (Ha et al. 2005). The enteric protozoan parasites Entamoeba spp., especially E. histolytica, E. polecki (Matsubayashi et al. 2015a, 2015b, 2016), and E. suis (Matsubayashi et al. 2014), were recently identified as the causative agent of diarrhea in pigs. E. polecki can be classified into four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…C. suis may cause transient diarrhea, which is often implicated by secondary pathogens such as bacteria and viruses [ 32 ], thus resulting in weight loss and managerial costs [ 33 ]. Additionally, this protozoon can lead to possible alterations of intestinal epithelium and gut microbiota and consequent diminished nutrient absorption [ 4 , 33 , 34 ]. This apicomplexan protozoon affects mainly suckling piglets, which are unable to mount an adequate primary immune response [ 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. suis may cause transient diarrhea, which is often implicated by secondary pathogens such as bacteria and viruses [ 32 ], thus resulting in weight loss and managerial costs [ 33 ]. Additionally, this protozoon can lead to possible alterations of intestinal epithelium and gut microbiota and consequent diminished nutrient absorption [ 4 , 33 , 34 ]. This apicomplexan protozoon affects mainly suckling piglets, which are unable to mount an adequate primary immune response [ 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study on pig farms in Tangerang, West Java, detected 17.3% of E. polecki ST3 (Wardhana et al 2020). Similarly, E. polecki ST3 has been found in pigs in the Honshu Islands, Japan (Komatsu et al 2019). The results of the exploration of pig samples from Kupang also found E. coli (30%) that occurred in Baureta (7%), Nesi Paraf (8%), Penfui (4%), Fatukoa (5%), and Binilaka (6%).…”
Section: Resultsmentioning
confidence: 88%
“…non-pathogenic to swine; however, E. suis and E. polecki have been found to cause severe enteritis. Entamoeba suis is supposed to induce hemorrhagic colitis by invading the lamina propria (Matsubayashi et al 2019). Moreover, E. polecki ST1 and ST3 are associated with proliferative enteritis caused by Lawsonia intracellularis (Matsubayashi et al 2015a(Matsubayashi et al , 2015b(Matsubayashi et al , 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is primarily due to damage to the villi and surface area of the small intestine, which impairs proper nutrient absorption. Additionally, C. suis has the potential to alter the intestinal epithelium and gut microbiota, resulting in decreased nutrient absorption [22,50]. Studies in gnotobiotic piglets suggested that C. suis is the primary pathogen [13], while co-infections with bacteria (e.g.…”
Section: Discussionmentioning
confidence: 99%